DenseNet based skin lesion classification and melanoma detection - Munaf, Arifuzzaman; Hoque, Ariful; Jawwad, Kazi Asif (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.